ANALISIS KEBUTUHAN SINERGITAS PENELITIAN DAN PENGABDIAN PADA MASYARAKAT SERTA PENGEMBANGAN PEMBELAJARAN - Boeriswati, Endry (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
There have been several challenges in facing the era of industrial revolution 4.0. namely "Artificial Intelligence (AI), data and information (big data), cloud computing (cloud technology), internet, digital money (bitcoin), social media to data security are challenges that must be faced by college graduates today. Industry 4.0 holds a commitment to increase flexibility in manufacturing, in bulk, with better quality and productivity, resulting in rapid changes experienced by society, namely the rapid development of information technology that has a lot of impacts on human life both positive and negative. which is very strategic in the midst of its community, which must be able to provide enlightenment for the surrounding community, nation and state.